CONDITIONS OF CLINICAL SYMPTOMS AND LIFE OF VANAME SHRIMP IN PREVENTION OF Vibrio alginolyticus INFECTION USING MIANA LEAF EXTRACT (Journal of Fish Health, 2021)
This study aims to determine the clinical symptoms and survival of white vaname shrimp in the prevention of Vibrio alginolyticus infection using miana leaf extract. The study consisted of 4 treatments and 3 replications. The treatments in this study were 1 treatment and 3 treatments using different concentrations of bacteria, namely 103 CFU/ml, 105 CFU/ml, and 107 CFU/ml. The research was carried out in June-July 2020 at the Hatchery Laboratory of the Faculty of Marine and Fisheries Sciences, Hasanuddin University. Data analysis used descriptive analysis and analysis of variance (ANOVA). The results showed that A (control) shrimp was under normal conditions, treatment B (103 CFU/ml) was red, treated C (105 CFU/ml) was red and had necrosis of the body, and treatment D (107 CFU/ml) was shrimp. reddening, necrosis of tail and body segments. The results of data analysis showed that the use of miana leaf extract had a significant effect (p